TINJAUAN PROSEDUR PENGAJUAN COST ALLOWANCE ATAS PERJALANAN DINAS DRIVER PT. GRAHAPRIMA SUKSESMANDIRI TBK - Salwa Natalia Asih (2023)
Cost allowance are important in Grahaprima Suksesmandiri Tbk Corp, because the allowance costs are closely related to the driver's journey in carrying out his duties. The final task is to get an in-depth description from The Review of Cost allowance Application Procedures For Driver's Travel in Grahaprima Suksesmandiri Tbk Corp. In the review of cost allowance application procedures, it is explained about how the issuance of a duty letter, the calculation of the target use allowance, the granting of Allowance to Drivers, to the responsibility of the driver in the use of the cost allowance already given. Based on the discussion about the review of cost allowance application procedures for driver's travel in Grahaprima Suksesmandiri Tbk Corp, it is quite good and effective. Keywords: Cost allowance, Official Travel, Responsibility.